2019
DOI: 10.26442/00403660.2019.01.000032
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of arterial hypertension and reduced renal function in a population 25-45 years

Abstract: Aim. To study relationships of reduced renal function with hypertension and other cardiometabolic risk factors in persons aged 25-45 years. Materials and methods. A cross-sectional population study of one of the typical district of Novosibirsk (Russia) was performed during 2013-2016 years. The study included 468 men and 606 women aged 25-45 years. Blood pressure (BP), waist circumference (WC), blood lipids, glucose, creatinine were measured. Glomerular filtration rate (GFR) was calculated with the formula CKD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Our findings are in line with a relatively low prevalence of CKD in Norway (3.3% in the HUNT study from central Norway) compared to other European counties in a multi-site comparison of adults aged 45–64 where prevalence ranged from 3 to 19% [ 3 ] while the estimates for Russia are also in the lower range for this study. A previous population-based study from Novosibirsk also indicated low prevalence of reduced eGFR (0.3% of the study sample) [ 19 ], however given the study was among young adults (aged 25–45 years) it is hard to draw conclusions from this as to prevalence at older ages. The finding that CKD prevalence is not high in Russia compared to International studies is perhaps surprising given the very high burden of CVD mortality in Russia.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Our findings are in line with a relatively low prevalence of CKD in Norway (3.3% in the HUNT study from central Norway) compared to other European counties in a multi-site comparison of adults aged 45–64 where prevalence ranged from 3 to 19% [ 3 ] while the estimates for Russia are also in the lower range for this study. A previous population-based study from Novosibirsk also indicated low prevalence of reduced eGFR (0.3% of the study sample) [ 19 ], however given the study was among young adults (aged 25–45 years) it is hard to draw conclusions from this as to prevalence at older ages. The finding that CKD prevalence is not high in Russia compared to International studies is perhaps surprising given the very high burden of CVD mortality in Russia.…”
Section: Discussionmentioning
confidence: 87%
“…Recent population studies in Russia have shown a high prevalence of risk factors for CKD - hypertension [ 12 , 13 ], diabetes [ 14 – 17 ] and obesity [ 12 , 18 ] - all indicating the burden of CKD is also likely to be high. One population-based study from the city of Novosibirsk (2013–2016) has investigated estimated glomerular filtration rate (eGFR) among 1064 adults aged 25–45 [ 19 ]. In this sample mildly reduced kidney function (eGFR< 90 ml/min/1.73m 2 ) was found in 9.8% of men and 34% of women [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation